Pharmacokinetic, partial pharmacodynamic and initial safety analysis of (−)-epicatechin in healthy volunteers. Issue 3 (19th January 2015) - Barnett, Christopher F.; Moreno-Ulloa, Aldo; Shiva, Sruti; Ramirez-Sanchez, Israel; Taub, Pam R.; Su, Yongxuan; Ceballos, Guillermo; Dugar, Sundeep; Schreiner, George; Villarreal, Francisco
Abstract : (−)-Epicatechin ((−)-EPI), a naturally occurring flavanol, has emerged as a likely candidate for cocoa-based product reported reductions in cardiometabolic risk. Abstract : (−)-Epicatechin ((−)-EPI), a naturally occurring flavanol, has emerged as a likely candidate for cocoa-based product reported reductions in cardiometabolic risk. The present study aimed to determine the safety, tolerability, pharmacokinetics and pharmacodynamics of purified (−)-EPI administered to healthy volunteers. In this phase I, open-label, two-part single- and multiple-dose study, subjects received either a single dose ( n = 9) of 50, 100 or 200 mg or multiple doses ( n = 8) of 50 mg daily (q.d.) or twice daily (b.i.d) for 5 days. Blood was collected at 0, 0.5, 1, 2, 4 and 6 h after (−)-EPI administration in the single and multiple dose groups (blood collection repeated in day 5). Samples were analyzed by HPLC-HR-ESI-MS for EPI and metabolite quantification. In the q.d. and b.i.d. groups, blood samples were analyzed for NO surrogates and follistatin levels as well as, platelet mitochondrial complexes I, V and citrate synthase activity levels. (−)-EPI was well tolerated and readily absorbed with further phase 2 metabolism. On day 5, in the q.d. and b.i.d. groups, there were significant increases in plasma nitrite of 30% and 17%, respectively. In the q.d. group on day 5 vs. day 1, platelet mitochondrial complexes I, IV and citrate synthase activities demonstrated a significant increase of ∼92, 62 and 8%, respectively. Average day 5 follistatin AUC levels were ∼2.5 fold higher vs. day 1 AUC levels in the b.i.d. group. (−)-EPI was safe to use, with no observed adverse effects, and our findings suggest that increases in NO metabolites, mitochondrial enzyme function and plasma follistatin levels may underlie some of the beneficial effects of cocoa products or (−)-EPI as reported in other studies.